Safety and efficacy studies of kyphoplasty, mesh-container-plasty, and pedicle screw fixation plus vertebroplasty for thoracolumbar osteoporotic vertebral burst fractures - Yimin Li; Yunfan Qian; Guangjie Shen; Chengxuan Tang; Xiqiang Zhong; Shaoqi He (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Percutaneous kyphoplasty (PKP), percutaneous mesh-container-plasty (PMCP), and pedicle screw fixation plus vertebroplasty (PSFV) were three methods for osteoporotic vertebral burst fractures (OVBF). The purpose of the current study was to evaluate the clinical safety and efficacy of PKP, PMCP, and PSFV for OVBFs. Methods This retrospective study included 338 consecutive patients with thoracolumbar OVBFs who underwent PKP (n = 111), PMCP (n = 109), or PSFV (n = 118) and compared their epidemiological data, surgical outcomes, and clinical and radiological features. Clinical evaluations of VAS and ODI and radiological evaluations of height restoration, deformity correction, cement leakage, and canal compromise were calculated preoperatively, postoperatively, and 2 years postoperatively. Results Cement leakage (31/111 vs. 13/109 and 16/118, P < 0.05) was significantly higher in group PKP than in groups PSFV and PMCP. VAS and ODI scores improved postoperatively from 7.04 ± 1.15 and 67.11 ± 13.49 to 2.27 ± 1.04 and 22.00 ± 11.20, respectively, in group PKP (P < 0.05); from 7.04 ± 1.29 and 67.26 ± 12.79 to 2.17 ± 0.98 and 21.01 ± 7.90, respectively, in group PMCP (P < 0.05); and from 7.10 ± 1.37 and 67.36 ± 13.11 to 3.19 ± 1.06 and 33.81 ± 8.81, respectively, in the PSFV group (P < 0.05). Moreover, postoperative VAS and ODI scores were significantly higher in group PSFV than in groups PKP and PMCP (P < 0.05). However, VAS scores were not significantly different in the three groups 2 years postoperatively (P > 0.05). Postoperative anterior (81.04 ± 10.18% and 87.51 ± 8.94% vs. 93.46 ± 6.42%, P < 0.05) and middle vertebral body height ratio (83.01 ± 10.16% and 87.79 ± 11.62% vs. 92.38 ± 6.00%, P < 0.05) were significantly higher in group PSFV than in groups PMCP and PKP. Postoperatively, Cobb angle (10.04 ± 4.26° and 8.16 ± 5.76° vs. 4.97 ± 4.60°, P < 0.05) and canal compromise (20.76 ± 6.32 and 19.85 ± 6.18 vs. 10.18 ± 6.99, P < 0.05) were significantly lower in group PSFV than in groups PMCP and PKP. Conclusion Despite relatively worse radiological results, PMCP is a safe and minimally invasive surgical method that can obtain better short-term clinical results than PKP and PSFV for OVBFs.